4D-CTA in Neurovascular Disease: A Review - Kortman, H.G.J.; Smit, E.J.; Oei, M.T.H.; Manniesing, R.; Prokop, M.; Meijer, F.J.A. (American Journal of Neuroradiology, 2015)
SUMMARY: CT angiography is a widely used technique for the noninvasive evaluation of neurovascular pathology. Because CTA is a snapshot of arterial contrast enhancement, information on flow dynamics is limited. Dynamic CTA techniques, also referred to as 4D-CTA, have become available for clinical practice in recent years. This article provides a description of 4D-CTA techniques and a review of the available literature on the application of 4D-CTA for the evaluation of intracranial vascular malformations and hemorrhagic and ischemic stroke. Most of the research performed to date consists of observational cohort studies or descriptive case series. These studies show that intracranial vascular malformations can be adequately depicted and classified by 4D-CTA, with DSA as the reference standard. In ischemic stroke, 4D-CTA better estimates thrombus burden and the presence of collateral vessels than conventional CTA. In intracranial hemorrhage, 4D-CTA improves the detection of the “spot” sign, which represents active ongoing bleeding.dAVFdural arteriovenous fistulaTI-CTAtiming-invariant CTA